A veterinary digital anatomical database. - Snell, J. R. (American Medical Informatics Association, 1991)
This paper describes the Veterinary Digital Anatomical Database Project. The purpose of the project is to investigate the construction and use of digitally stored anatomical models. We will be discussing the overall project goals and the results to date. Digital anatomical models are 3 dimensional, solid model representations of normal anatomy. The digital representations are electronically stored and can be manipulated and displayed on a computer graphics workstation. A digital database of anatomical structures can be used in conjunction with gross dissection in teaching normal anatomy to first year students in the professional curriculum. The computer model gives students the opportunity to "discover" relationships between anatomical structures that may have been destroyed or may not be obvious in the gross dissection. By using a digital database, the student will have the ability to view and manipulate anatomical structures in ways that are not available through interactive video disk (IVD). IVD constrains the student to preselected views and sections stored on the disk.